Computation and field experiment validation of greenhouse energy load using building energy simulation model - Ha, Taehwan; Lee, In-bok; Kwon, Kyeong-seok; Hong, Se-Woon (International Journal of Agricultural and Biological Engineering, 2015)
Greenhouse Building Energy Simulation (BES) models were developed to estimate the energy load using TRNSYS (ver. 16, University of Wisconsin, USA), a commercial BES program. Validation was conducted based on data recorded during field experiments. The BES greenhouse modeling is reliable, as validation showed 5.2% and 5.5% compared with two field experiments, respectively. As the next step, the heating characteristics of the greenhouses were analyzed to predict the maximum and annual total heating loads based on the greenhouse types and target locations in the Republic of Korea using the validated greenhouse model. The BES-computed results indicated that the annual heating load was greatly affected by the local climate conditions of the target region. The annual heating load of greenhouses located in Chuncheon, the northernmost region, was 44.6% higher than greenhouses in Jeju, the southernmost area among the studied regions. The regression models for prediction of maximum heating load of Venlo type greenhouse and widespan type greenhouse were developed based on the BES computed results to easily predict maximum heating load at field and they explained nearly 95% and 80 % of the variance in the data set used, respectively, with the predictor variables. Then a BES model of geothermal energy system was additionally designed and incorporated into the BES greenhouse model. The feasibility of the geothermal energy system for greenhouse was estimated through economic analysis.Keywords: greenhouse, building energy simulation (BES), energy load, dynamic analysis, geothermal energy, heating loadDOI: 10.3965/j.ijabe.20150806.2037Citation: Ha T, Lee I B, Kwon K S, Hong S W. Computation and field experiment validation of greenhouse energy load using Building Energy Simulation model. Int J Agric & Biol Eng, 2015; 8(6): 116－127.